Tracking of Cardiorespiratory Fitness from Childhood to Mid-adulthood - Guo, Jia (MOSBY-ELSEVIER, 2025)
High cardiorespiratory fitness (CRF) in adulthood is important for survival from major chronic diseases and preserving good health. We examined how childhood CRF tracks, or persists, into adulthood. Among a cohort of 748 school children followed over 34 years, we found child CRF correlated with young- (r = 0.30) and mid-adulthood (r = 0.16) CRF.